Pathogenic ecological characteristics of PCV2 in large-scale pig farms in China affected by African swine fever in the surroundings from 2018 to 2021 - Li, Chunqi; Liu, Guoping; Tong, Ke; Wang, Yan; Li, Tong; Tan, Xu; Yang, Jie; Yang, Xiaolin; Guo, Liwei; Zeng, Jianguo (Frontiers in Microbiology, 2023)
Porcine circovirus type 2 (PCV2) has been identified as the causal agent of postweaning multisystemic wasting syndrome (PMWS), an economically important multifactorial disease of the swine industry worldwide. This research designed a dual nested polymerase chain reaction (PCR) detection method to simultaneously monitor porcine circovirus type 2 (PCV2) and PCV3. The limit of detection (LoD) of sensitivity for PCV2 and PCV3 was ten copies/mL for both viruses. There was no cross-reaction with any other porcine pathogens tested and no non-specific amplification. The coincidence and repetition rates were 100%. Through the systematic and clinical sampling, 15,130 samples from 30 large-scale pig farms in eight provinces (Hubei, Hunan, Henan, Jiangxi, Shanxi, Guangdong, Hainan, and Heilongjiang) were subjected to early warning surveillance and/or clinical diagnosis. The results revealed that the overall positive rates of PCV3 and PCV2 were 0% and 28.29%, respectively, with the lowest level recorded in Jiangxi province. The highest carrying rate was observed in Hainan province. Pigs at different ages displayed varying carrying rates: fattening pigs and reserve pigs had the highest and the lowest carrying rates. In addition, the detoxification rates of colostrum, semen, and nasal, anal, and vulval swabs were tested. The colostrum, anal swabs, and semen had higher toxicity rates; these were followed by the vulval and nasal swabs that had toxicity rates. Furthermore, a high blood virus-carrying rate was detected in moribund pigs, especially in pigs with fever and red skin. As to the virus-carrying rate in the pig organs received from clinical necropsy, the highest rate was found in placental tissue, followed by the kidneys, and the virus also was detected in lymphoid organs, liver, stomach, and intestines. The PCV2-positive samples were sequenced and compared to reveal the molecular epidemic dynamics of PCV2. The results indicated four major branches, namely, PCV2a, PCV2b, PCV2c, and PCV2d, concerning PCV2 molecular epidemiology in China, with PCV2a, PCV2b, and PCV2d dominating. The results obtained in this study elucidated the molecular epidemiology, transmission, and viremia of PCV and provided new ideas for developing comprehensive PCV control technologies to begin eliminating the disease caused by PCV by cleaning pig farms.